Holocene extinctions - Turvey, Sam. (Oxford : Oxford University Press, 2009)
'Holocene Extinctions' describes and analyses the range and duration of global extinction events that have occurred since the end of the last Ice Age glaciation, as well as their relationship to both previous and subsequent species losses.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Extinction (Biology); Paleontology -- Holocene